2008
DOI: 10.1021/ac801641a
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Plasma Probe for Ambient Desorption Ionization

Abstract: A low-temperature plasma (LTP) probe has been developed for ambient desorption ionization. An ac electric field is used to induce a dielectric barrier discharge through use of a specially designed electrode configuration. The low-temperature plasma is extracted from the probe where it interacts directly with the sample being analyzed, desorbing and ionizing surface molecules in the ambient environment. This allows experiments to be performed without damage to the sample or underlying substrate and, in the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
733
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 661 publications
(749 citation statements)
references
References 35 publications
11
733
0
1
Order By: Relevance
“…Additionally, the tolerance to positioning in negative ion mode was about 12 × 6 × 5 mm (x, y, z). Compared with paper spray and other methods, [17,18] a comparable sampling area was achieved, although the tolerances of DSI in positive and negative ion mode were not in exact accordance. Therefore, it is not difficult to adjust the tip to obtain a good signal when the corner is positioned within an area of approximately 10 × 6 × 5 mm (x, y, z) in front of the inlet of an instrument.…”
Section: Tolerance To Varied Source Positionmentioning
confidence: 91%
See 1 more Smart Citation
“…Additionally, the tolerance to positioning in negative ion mode was about 12 × 6 × 5 mm (x, y, z). Compared with paper spray and other methods, [17,18] a comparable sampling area was achieved, although the tolerances of DSI in positive and negative ion mode were not in exact accordance. Therefore, it is not difficult to adjust the tip to obtain a good signal when the corner is positioned within an area of approximately 10 × 6 × 5 mm (x, y, z) in front of the inlet of an instrument.…”
Section: Tolerance To Varied Source Positionmentioning
confidence: 91%
“…However, in the case of a real-time monitoring experiment, characterized as short reaction time, the trade-off needs not to be considered, and the optimization of parameters is easy, as compared with DESI and LTP. [8,18] Thus, the favorable spray angle of 2°was selected as a compromise between spray time and ion intensity.…”
Section: Spray Timementioning
confidence: 99%
“…Recently, breakthrough of mass [36,37]. After DESI, more than 20 ambient ionization techniques were further developed, including direct analysis in real time (DART) [38,39], surface desorption atmospheric pressure chemical ionization (DAPCI) [40,41], extractive electrospray ionization (EESI) [42], low temperature plasma (LTP) [43,44], and easy ambient sonic ionization (EASI) [45]. Two major advantages of ambient mass spectrometry are minimal sample pre-treatment and high-throughput MS analysis [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies were performed by Harper et al [164] where the LTP ionization source was interfaced with a mass spectrometer to perform surface analysis at ambient pressure and simply required an alternating current (AC) power supply and discharge gas to produce ions from different surfaces. The simple ionization source generates a low temperature plasma, with temperatures ranging from 25-30°C, that is extruded from a glass probe and has nondestructive properties.…”
Section: Low Temperature Plasmamentioning
confidence: 99%
“…Currently, studies have found LTP coupled to a mass spectrometer to be a successful ionization technique for explosives and illicit drugs; however, there has been little to no studies reporting the use of an LTP source with an IMS detector. A home-built LTP source was developed in order to characterize the ionization source and further pursue the ability to interface it with a home-built IMS system using a power source similar to that of Harper and colleagues [164], shown in Figure 4.3 (a). The home-built power supply allowed for variable frequency and voltages to be used in order to determine the best ionization setting when using different discharge gases which included helium, air, and nitrogen; it was concluded that helium provided the best visual and ionizing plasma plume and was used for the remainder of this study (Figure 4.3 (b)).…”
Section: Low Temperature Plasmamentioning
confidence: 99%